An internal iliac artery ligation technique for bleeding control in the placenta accreta spectrum disorder - Riu, Deviana Soraya; Sunarno, Isharyah; Pelupessy, Nugraha; Bakri, Syarif; Muchtar, Faisal; Andi Adil; Muhiddin, Rachmawati (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objective: To assess the contribution of internal iliac artery ligation to bleeding control during surgery. Methods: This retrospective study used secondary data from medical records. All patients diagnosed with PASD from January 2019 – to December 2022 were included in this study. Participants were grouped based on operation technique, and the blood loss and operative duration were evaluated. The tests used were the Kruskal-Wallis and the Mann-Whitney U tests. Results: 108 PAS patients were discovered. The most age group was between 20-35 years with parity of more than or equal to 4, history of Cesarean section once, gestational age at termination 34-36 weeks, and maternal death in 7 out of 101 cases. There were 49 resections, 13 resections with internal iliac artery ligation, 34 hysterectomies, and 12 hysterectomies with internal iliac artery ligation. There was no difference in bleeding and operative duration between resection vs. resection with internal iliac artery ligation (p: 0.113; p: 0.639), hysterectomy vs. a hysterectomy with internal iliac artery ligation ((p:0.052; P:0.723), and resection with ligation vs hystetectomy with the internal iliac artery ligation (p:0.052; p:0.723). Bleeding and operative duration differed significantly between resection vs. hysterectomy (p:0.002; p:0.013). All patients underwent tourniquet placement. Conclusion An Internal iliac artery ligation was not shown to reduce bleeding in treating PASD. Keywords: accreta, internal iliac artery, placenta .